Threats In International Logistics – Study During Covid-19 Pandemic Time - Michał Kot (Communications of International Proceedings, 2021)
International logistics processses and global supply chains have been interrupted or even broken by the results of Covid-19 pandemia. The enterprises have to forced new threats for their functioning. Therefore, the main objective of the study is to identify the risk factors that have the greatest impact on destabilizing the international logistics of enterprises and their supply chains. In addition, the research intends to show the attitude of enterprises to outsourcing and defines the most frequently used indicators; they are used as measures in the processes of measuring the level of achievement of the organization's goals (KPI) by respondents. The research sample covers 86 enterprises of all sizes operating in various economic sectors. The results of the research create a list of the most prevalent threats occurring in the economic environment, the ways in which the enterprise prevents the occurrence of such a risk and the ways of dealing with the already existing risk. The findings of the study also reveal the respondents' attitude towards outsourcing.
Keywords: International Logistics; Threats; Management; Risk